EDUCATIONAL EVOLUTION: SUSTAINABLE BETURNMENT WITH COUNTRY IN THE DEVELOPMENT OF THE TRAINER - Rizal, Mohammad Syifaur; Aliwafa, Aliwafa; Sugiono, Sugiono; R, Abu Hasan Agus; Hakim, Lukman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
In  this  study,  the  researchers  wanted  to  discuss  how  sustainable improvements  were  made  by  guardians  in  the  development  of  the  nursery. Researchers  use  a  qualitative  method  that  aims  to  explain  the  truth  of  a phenomenon that has the aim of obtaining objective data. Based on the results of  the  research,  it  can  be  concluded  that  in  carrying  out  continuous improvement with the guardian in the development of the foster care there are several steps that have been applied among them: (a) to know closer with the centurion,  to  engage  in  close  proximity  with  the  clergyman  as  a  guardian requires  challenges  that  must  be  overcome  on  its  own.  Understanding  the unique personality of each centri is pleasant when we are able to communicate with  the  heart.  (b)  Loving  the  mother-in-law,  the  guardian  must  provide emotional support as  a  key aspect. Listening attentively to their stories,  their excitement, or their  concerns is a first step in building a strong bond. One of the  things  to  pay  attention  to  is  the  fulfilment  of  basic  needs,  such  as  food, shelter,  and  clothing.  The  guardian  should  also  ensure  that  the  guardian  has adequate access to  educational facilities and learning facilities. (d) the  prayer of  the  clergyman,  the  guardian  is  not  only  limited  to  the  physical  and educational  aspects,  but  also  includes  attention  to  the  spiritual  dimension  of the centurion.